STRATEGI OPTIMALISASI MOTORIK HALUS ANAK USIA DINI MELALUI AKTIVITAS PAPER CRAFT 3M (MELIPAT, MENGGUNTING, DAN MENEMPEL) DI TK KARTINI WANGKAL - Supriyatin; Indah Kharismawati; Trio Suwargono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Fine motor skills play an important role in early childhood learning readiness. This study aimed to optimize children’s fine motor skills through a learning strategy based on Paper Craft 3M activities (folding, cutting, and pasting). The research employed two-cycle Classroom Action Research (CAR) consisting of planning, action, observation, and reflection, involving 20 children aged 4–5 years at Kartini Wangkal Kindergarten, Probolinggo Regency. Data were collected through structured observation using a fine motor development assessment sheet. The results showed an improvement in fine motor skills, from the pre-cycle stage with no children achieving the Developing as Expected (DE) and Very Well Developed (VWD) categories, to 20% of children reaching DE in Cycle I, and a significant increase in Cycle II with 75% achieving DE and 25% achieving VWD. These findings indicate that Paper Craft 3M activities are effective in optimizing fine motor skills in early childhood.